Anemia in children with chronic renal failure Special attention erythrocyte indices and iron deficiency anemia - Adi Suryanto B; Partini P Trihono; Agus Firmansyah (Indonesian Pediatric Society Publishing House, 2016)
Background Anemia in chronic renal failure (CRF) has been proved to influence the quality of life, increasing morbidity and mortality. Early diagnosis and prompt treatments of anemia are mandatory to manage CRF appopriately. So far data of anemia in CRF in Indonesia is limited. Objective To find out the profile of anemia in children with CRF at Cipto Mangunkusumo Hospital (CMH), Jakarta, with special atten- tion in erythrocyte indices and iron deficiency anemia. Methods Cross-sectional descriptive study was carried out on patients with CRF and anemia in CMH since October 2003 to April 2004. Results There were 20 CRF patients, aged between 1 year 3 month- 15 year old, mostly were above 10 year old, 11 patients were males and 9 were females. The most frequent etiologies were urinary tract infection (UTI) in 10 cases and nephrotic syndrome in 6 cases. Of those 20 patients, 14 suffered from anemia with erythrocyte indices, normochrome normocytic in 9 patients and hypochrome microcytic in 5 patients. Of 14 anemic patients only 1 patient suf- fered from iron deficiency anemia of less than 10 mg/l and transferin saturation of less than 12%. Based on serum iron (SI) concentra- tion only, 7 patients were diagnosed as having iron deficiency ane- mia. Conclusion Most patients with chronic renal failure have normochrome normocytic anemia. Hypochromic microcytic iron deficiency anemia is scarcely found in this group of patients.